Pengaruh Kompetensi Profesional Guru Terhadap Hasil Belajar Siswa Pendidikan Agama Islam Tingkat Madrasah Aliyah - Didit Darmawan; Muhammad Izzul Haq (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
Education plays a strategic role in developing competent human resources as well as in shaping character, ethics, and moral values, particularly through Islamic Religious Education in Madrasah Aliyah. MA students today face the challenges of the digital age, including exposure to negative content and uncontrolled use of social media, which have the potential to undermine moral integrity and learning outcomes. This study aims to examine the contribution of PAI teachers' professional competence to student learning outcomes. A qualitative approach was used with a literature study design, through a systematic review of scientific articles, journals, and previous studies related to teacher competence and student learning outcomes. The analysis was conducted by identifying, selecting, and grouping information to draw conceptual conclusions. The findings show that teachers with high professional competence are able to master the material in depth, integrate Islamic values into learning, design effective teaching strategies, motivate students, and create a conducive learning environment. Teachers' professional competence has been proven to have a positive and significant impact on learning outcomes in the cognitive, affective, and psychomotor domains, as well as supporting the formation of students' character and morals. The implications of this study emphasize the importance of continuous professional development for teachers through training, supervision, and strengthening of pedagogical capacity, so that Islamic Education in Madrasah Aliyah can produce graduates who excel academically and are mature in spirituality and morality.